PENGARUH KUALITAS PRODUK DAN LOKASI TERHADAP KEPUASAN KONSUMEN MELALUI MINAT BELI SEBAGAI VARIABEL INTERVENING PADA TOKO CANTIKA PANJI SITUBONDO - Marham, Muhammad; Arief, Mohammad Yahya; Soeliha, Siti (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
The beauty that prevails in society creates a vision of beauty that becomes the standard for calling a woman beautiful. The use of skin care products is the most popular thing, but some skin care products have to face a lot of competition in the world market because of the large number of products available to the general public. The purpose of this study is to determine the effect of product quality and location on consumer satisfaction through purchase intention as an intervening variable at Panji Situbondo Cantika shop. The population in this study are all consumers who come to Toko Cantika. random sampling method (simple probability sampling) regardless of strata in the population in this study. In taking this sample using a presentation level of 10%. Data analysis and hypothesis testing in this study used the Structural-partial Least square equation model (PLS-SEM). The results of hypothesis testing using the smart PLS 3.0 application show that product quality has a significant positive effect on purchase intention, location has a significant positive effect on purchase intention, product quality has a significant positive effect on customer satisfaction, location has a significant positive effect on customer satisfaction, and purchase intention has a significant positive effect on consumer satisfaction. Product quality on consumer satisfaction through purchase intention has a significant positive effect and location on consumer satisfaction through purchase intention has a significant positive effect.